The Effect of Long Term Irrigation by Treated Effluent on Boron Accumulation in Soil and Citrus Plants - Daba’an, Ra’fat Abu; Al-Najar, Husam (Asian Review of Environmental and Earth Sciences, 2018)
The aim of the current research is to assess the long term effect of boron concentration in treated wastewater on citrus plants cultivated in various soil textures. Boron concentrations of treated wastewater used in sandy and clay soil were 1.45±0.37 and 1.03±0.45 mg/l, respectively. In sandy soil, Boron concentrations were 0.53 ± 0.15 and 3.94 ± 0.97 mg/ kg soil showed significant variation at p < 0.05 between the top 0- 30 and the second layer 30- 60 cm, respectively, while the leaves of citrus have boron concentration of 104.1 mg/kg dry weight. In clay soil boron concentrations were 0.79 mg/kg in both soil layers and in citrus leaves was 267.1 mg/kg dry weight which slightly exceeds the recommended limits 250 mg/kg dry weight. Therefore, the fate of Boron depends mainly on the soil texture; in the sandy soil leaching to deeper layers is occurred, while boron is accumulated in clay soil and citrus leaves. Thus, the municipal treated wastewater could be used safely to irrigate citrus cultivated in sandy soil textures.